Applying Modelica Tools to System Dynamics Based Learning Games: Project Management Game. (26th October 2016) - Miettinen, Tuomas; Salmi, Juho; Gupta, Kunal; Koskela, Jussi; Kauttio, Janne; Karhela, Tommi; Ruutu, Sampsa
Abstract : Learning simulation games are interactive simulations with game characteristics. This paper presents a learning simulation game for EPCM (engineering, procurement, and construction management) project management training. The simulation model utilises system dynamics, which is a methodology for understanding the behaviour of dynamic complex systems of different domains using modelling and simulation. The system dynamics model in turn uses the equation-based Modelica modelling language: a system dynamics model created with the graphical user interface is converted to a pure Modelica model. Two Modelica environments, namely, OpenModelica and the custom Modelica solver, have been used to simulate the generated Modelica model. The focus of this article is on how generic systems modelling and simulation platforms such as Modelica based environments can be utilised in developing a learning simulation game: what benefits do they bring and what disadvantages do they have? On the one hand, it is evaluated how the Modelica language as such is suitable for being used in a learning game development. On the other hand, the suitability of the selected implementation environments, that is, OpenModelica, the custom Modelica solver, Simantics, and Simupedia, is evaluated. The paper also shortly presents how the project management game was received by its players.